TECHNOLOGY OF DYNAMIC DATABASES CREATION WITH THE ENCLOSED STRUCTURES IN MS EXCEL ﻿ - Kravtsova, Л.В.; Kaminska, Н.Г.; Pulyaeva, А.В. (Journal of Information Technologies in Education (ITE), 2012)
In work questions of use of spreadsheets MS Excel for dynamic database creation with the enclosed structures are examined.